2022
DOI: 10.1088/1873-7005/ac4e7b
|View full text |Cite
|
Sign up to set email alerts
|

Entropy generation in electroosmotically aided peristaltic pumping of MoS2 Rabinowitsch nanofluid

Abstract: The main emphasis of this article is to compare the heat transfer performance of two different nanofluids i.e. Carboxy-Methyl-Cellulose(CMC)+water-based molybdenum dioxide(MoS2) nanofluid and kerosene oil-based molybdenum dioxide nanofluid during the fluid flow through a symmetric microchannel which is pumped by the mechanism of peristalsis and electroosmosis. The energy dissipated by Joule heating and viscous dissipation is also taken into account. An analysis of volumetric entropy generation is also conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Utilizing two distinct methods for nanofluid analysis, the silver−water nanofluid electro-osmotic movement that is controlled by peristalsis was investigated by [24]. [25] studied the electro-osmotically assisted peristaltic pressurization of the MoS 2 Rabinowitsch nanofluid and produced randomness. The use of novel nanofluids throughout clinical isolates to fight Staphylococcus aureus was investigated by [26].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing two distinct methods for nanofluid analysis, the silver−water nanofluid electro-osmotic movement that is controlled by peristalsis was investigated by [24]. [25] studied the electro-osmotically assisted peristaltic pressurization of the MoS 2 Rabinowitsch nanofluid and produced randomness. The use of novel nanofluids throughout clinical isolates to fight Staphylococcus aureus was investigated by [26].…”
Section: Introductionmentioning
confidence: 99%
“…The peristaltic flow of viscoelastic fluid with the Hartmann boundary layer effect is investigated by Ali et al [6]. Akram and Rashid discussed the peristaltic flow of Rabinowitsch and Williamson fluid respectively (see [7,8]). An experimental approach is discussed by Mirzaei et al [9] in dialysis machines of peristaltic slug flows.…”
Section: Introductionmentioning
confidence: 99%
“…Javed and Naz [6] considered the Jeffrey fluid for pumping flow in an asymmetric channel and observed that reverse pumping occurs near the channel walls. Other relevant studies on viscous fluid flows in channels have also been reported [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%